NIPAL4 is an important marker for clear cell renal cell carcinoma prognosis and immunotherapy - Shuyan Wei; Fang Lyu; Bei Qian; Yumei Tang; Qingliu He (Scientific Reports)
Abstract Clear cell renal cell carcinoma (ccRCC) poses significant clinical challenges due to its high metastatic rate at diagnosis and resistance to conventional therapies. The magnesium transporter NIPAL4, involved in lipid metabolism and magnesium ion homeostasis, has recently been implicated in cancer biology but remains understudied in ccRCC. In this study, we identifies NIPAL4 as a potential prognostic marker and therapeutic target in ccRCC. High NIPAL4 expression is associated with poor prognosis and contributes to tumor proliferation and migration. Bioinformatics analyses indicate that NIPAL4 is involved in critical pathways related to the extracellular matrix, lipid metabolism, and the TGF-β signaling pathway. Moreover, NIPAL4’s association with immune cell infiltration and immune checkpoint molecules highlights its potential as an immunotherapy marker. These findings warrant further investigation into NIPAL4’s role in ccRCC to develop more effective treatment strategies.